Zero-Voltage and Zero-Current Switching Buck-Boost Converter for PV Applications - Athulya P Prem; Sudhin Govind; Chinnu P Ravi (Institute of Advanced Engineering and Science, 2014)
A ZVS and ZCS buck boost converter is presented for PV panel applications. The salient points are that all the switching devices are under zero-current switching during turn-on and zero-voltage switching during turn-off. The active switches in the converter undergo zero-capacitive turn-on losses unlike switches in other soft-switched topologies. The switches do not experience any over voltage/over current stress proportional to load as in resonant converters. This soft-switching technique can also be applied to other classical switched mode power converters. A detailed analysis of the converter under steady state is discussed and simulation results obtained are presented.